Key Management for Secure Multicast over IPv6 Wireless Networks - Aye, Win; Siddiqi, Mohammad Umar (2006)
Multicasting is an efficient method for transmission and routing of packets to multiple destinations using fewer network resources. Along with widespread deployment of wireless networks, secure multicast over wireless networks is an important and challenging goal. In this paper, we extend the scope of a recent new key distribution scheme to a security framework that offers a novel solution for secure multicast over IPv6 wireless networks. Our key management framework includes two scenarios for securely distributing the group key and rekey messages for joining and leaving a mobile host in secure multicast group. In addition, we perform the security analysis and provide performance comparisons between our approach and two recently published scenarios. The benefits of our proposed techniques are that they minimize the number of transmissions required to rekey the multicast group and impose minimal storage requirements on the multicast group. In addition, our proposed schemes are also very desirable from the viewpoint of transmission bandwidth savings since an efficient rekeying mechanism is provided for membership changes and they significantly reduce the required bandwidth due to key updating in mobile networks. Moreover, they achieve the security and scalability requirements in wireless networks.